PENERAPAN MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA VIDEO ANIMASI POWTOON DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Yuliana Yuliana; Yoni Hermawan; Ai Nur Solihat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by the problem at SMAN 1 Cihaurbeuti, namely the low critical thinking skills of students. The method used is an experimental method with a Problem Based Learning learning model assisted by Powtoon animation videos. The research design uses a non-equivalent control group design, data collection techniques through description tests. The population in this study was all class XI IPS at SMAN 1 Cihaurbeuti, totaling 164 students. The samples used were class XI IPS 2, totaling 34 students as the Experiment class and class XI IPS 3, totaling 35 students as the Control class. The aim of this research is to determine the effect of applying the Problem Based Learning model assisted by Powtoon animated video media in improving students' critical thinking skills in the economics subject of international trade concepts.